Evaluation of the methodology for determining cycling flows in Lithuania - Zabielaitė-Skirmantė, Miglė; Burinskienė, Marija (International Conference “Environmental Engineering”, 2023)
Sustainable urban development is one of the most pressing issues in urban planning, and such development requires the promotion of sustainable traffic and the use of non-motorised means of transport. The main problem encountered is the lack of a methodology to easily identify existing cycling flows in the study area. Taking into account the lack of such a methodology, the paper analyses 3 methodologies for determining the bicycle flow in different land use areas of Vilnius city. A survey of the residents of the analysed areas was carried out in order to identify the factors that determine the choice of cycling trips. The study found that the proposed methodologies for determining cycling flow have a 20–40% error margin. The main factor that influences the choice to cycle is the attitude towards cycling as a leisure activity.